Míadṡlechtae : an old Irish law text on status - Manning, Gerald (Trinity College (Dublin, Ireland). Department of Irish and Celtic Studies, 2005)
This thesis consists of an attempt to provide a critical edition, translation and analysis of the material contained in the Old Irish status text entitled Míadṡlechtae. Míadṡlechtae is one of a number of early Irish law tracts that deal with the issue of status in early Irish society. In Ireland of the seventh eighth and ninth centuries a person’s legal standing and entitlements were dependent on a variety of parameters - political power, wealth and material resources or one’s level of achievement in the fields of ecclesiastical and secular learning.
Keywords: Irish, Ph.D.; Ph.D. Trinity College Dublin